Public Health Emerging and Re-emerging Issues - Anwarul Azim Majumder, Md; Kabir, Russell; Rahman, Sayeeda (IntechOpen, 2018)
The main aim of modern public health is to improve the quality of life and promote health for all. Public health deals with a wide range of individuals and collaborates with various organizations, departments, and agencies to improve health, forestall disease and promote well-being. The field of public health is constantly evolving in response to the needs of communities and populations that are facing demographic, epidemiological and technological challenges. To overcome these challenges, health professionals need to conduct research to generate evidence-based policies to improve the health of the community. Throughout the course of this book, a number of emerging and re-emerging public health issues from different countries are discussed and attempts are made to illustrate a balanced and evidence-based approach towards tackling major public health problems.